A Significant Genetic Admixture in Farmed Populations of the Noble Scallop Chlamys nobilis Revealed by Microsatellite DNA Analysis in Southern China - Ma, Haitao; Yu, Dongmei; Xiao, Shu; Qin, Yanping; Zhang, Yang; Li, Jun; Zhang, Yuehuan; Yu, Ziniu (Frontiers in Marine Science, 2021)
The noble scallop, Chlamys nobilis, is an important bivalve mollusk with high commercial value and is usually farmed in the waters of southern China. To date, very little is known about the genetic diversity and population structure of C. nobilis. In this study, 10 microsatellite loci of four farmed C. nobilis populations were compared with one another and compared wild population in southern China. A total of 83 alleles were found. Surprisingly, the level of genetic diversity of the farmed C. nobilis populations was higher than that of the wild population. Although the population genetic of wild population was completely in the Hardy–Weinberg equilibrium, due to heterozygote deficiency, significant deviations from the Hardy–Weinberg equilibrium were found in all farmed populations, suggesting a genetic admixture caused by the mixing of seeds from various hatcheries. The Fst and AMOVA values showed significant genetic differences between wild and farmed populations. The Bayesian assignment also confirmed that genetic admixture was significant and widespread in artificial breeding of C. nobilis. Furthermore, the UPGMA tree topology and PCA demonstrated that the genetic diversity of wild population can be clearly distinguished from farmed populations. In a nutshell, the findings of this study not only fill the knowledge gaps in genetic diversity of wild and farmed C. nobilis populations, but also serve as a guide for maintaining the genetic diversity of C. nobilis in both farmed and wild populations.